When Theatre Becomes Digital: A Theoretical Implication on Theatre Study Development in Indonesia - Meilinda, Meilinda; Puspa, Ratih (Universitas Airlangga, 2023)
The COVID-19 pandemic wrought havoc across various facets of human life, inducing transformative disruptions, notably in the domain of theatre. The traditional paradigm of live indoor performances, characterized by the dynamic interactions among actors, was rendered unsafe. In response, the digital space emerged as a viable alternative, not only in Indonesia but globally. This paradigm shift necessitates and begets new theories intrinsic to theatre in the digital realm. This article traces the historical trajectory and the ensuing transformations in digital theatre, offering insights into the anticipated outcomes of these changes within the realm of theatre and performance studies. The evolution of theatre in the digital space challenges established boundaries, rules, and theories, fundamentally altering conceptions related to actor relationships, the juxtaposition of physical and digital bodies, delineations between stage and backstage, considerations of identity, ideology, and the very essence of this nascent digital domain.